Dynamic of professionally important qualities’ changes in cadets of higher flight establishments - Kyrpenko, V.N. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: determination of dynamic of professionally important qualities changes in cadets- flighters in the course of study. Material: The research convered 223 cadets during 4 years’ study with the help of complex of prognosis-informational psychological methods. Testing was fulfilled at devices RKN and PPV-2. Results: it was found that at the end of studying temp of development of such qualities as quickness of psycho-motor skills’ mastering, ability to operate space images, distribution and re-switching of attention increase noticeably. Indicators of emotional stability, re-construction of psycho-motor skills, resistance to obstacles substantially reduce. Scope of attention, reproductive thinking, operative memory, coordination of movements, ability to work in forced temp change in negligible limits. As per prognosis stabilizing of most of professionally important qualities that is connected with over-tension of organism’s physiological reserves is envisaged. Conclusions: We have found steady positive dynamic of cognitive psychic processes’ development, reduction of some psycho-physiological and psycho-motor qualities’ development in last period of studying.